HUBUNGAN ANTARA BUDAYA ORGANISASI DAN MOTIVASI DENGAN KINERJA - Dwi Kartika Susanti (Universitas Negeri Jakarta, 2012)
The research aims to know about: (1) the correlation of organizational culture with job performance; (2) the correlation of motivation with job performance; (3) the correlation of both organizational culture and motivation with job performance. The research was done in state elementary school in Administrative City South Jakarta. The method of this research is quantitative description approach. The purpose of using this method was to analyze the correlation between two or more variable through hypotheses test and also to research social phenomena in real situation. The results of the research are answering the hypotheses: (1) There’s a positive correlation of organizational culture with job performance; (2) There’s a positive correlation of motivation with job performance; (3) There’s a significance correlation of both organizational culture and motivation with job performance. From the research result, it can be concluded that if organizational culture of State Elementary School’s Principal comfortable, job performance will also increase. The same thing also happens to motivation. Therefore, the Principals’ organizational culture and motivation ought to be improved in order to attain higher job performance. Finally, organizational culture and motivation can simultaneously improve job performance. If they are applied, the Principal can attain better job performance.